Desarrollo de un sistema bikefit de bajo costo mediante un análisis biomecánico (2021)
This project is focused on the development of an application to obtain biomechanical data from a cyclist, which will be used to determine the proper configuration of his bicycle. For this, OpenCV will be used, an artificial vision library that allows to generate video analysis and create image events, useful for obtaining the movement of joints and their respective dynamic angles. The project will test the usefulness of this technological tool by means of a case study, where an analysis of the oscillations of the ankle of a cyclist who presents a change of position of the foot in the pedaling as she increases her speed.